The increase in pulmonary arterial pressure caused by hypoxia depends on iron status. - Smith, T; Balanos, G; Croft, Q; Talbot, N; Dorrington, K; Ratcliffe, P; Robbins, P (2008)
Hypoxia is a major cause of pulmonary hypertension. Gene expression activated by the transcription factor hypoxia-inducible factor (HIF) is central to this process. The oxygen-sensing iron-dependent dioxygenase enzymes that regulate HIF are highly sensitive to varying iron availability. It is unknown whether iron similarly influences the pulmonary vasculature. This human physiology study aimed to determine whether varying iron availability affects pulmonary arterial pressure and the pulmonary vascular response to hypoxia, as predicted biochemically by the role of HIF. In a controlled crossover study, 16 healthy iron-replete volunteers undertook two separate protocols. The 'Iron Protocol' studied the effects of an intravenous infusion of iron on the pulmonary vascular response to 8 h of sustained hypoxia. The 'Desferrioxamine Protocol' examined the effects of an 8 h intravenous infusion of the iron chelator desferrioxamine on the pulmonary circulation. Primary outcome measures were pulmonary artery systolic pressure (PASP) and the PASP response to acute hypoxia (DeltaPASP), assessed by Doppler echocardiography. In the Iron Protocol, infusion of iron abolished or greatly reduced both the elevation in baseline PASP (P < 0.001) and the enhanced sensitivity of the pulmonary vasculature to acute hypoxia (P = 0.002) that are induced by exposure to sustained hypoxia. In the Desferrioxamine Protocol, desferrioxamine significantly elevated both PASP (P < 0.001) and DeltaPASP (P = 0.01). We conclude that iron availability modifies pulmonary arterial pressure and pulmonary vascular responses to hypoxia. Further research should investigate the potential for therapeutic manipulation of iron status in the management of hypoxic pulmonary hypertensive disease.